2022
DOI: 10.1186/s12302-022-00656-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated use of biomarkers to assess the impact of heavy metal pollution on Solea aegyptiaca fish in Lake Qarun

Abstract: Background Biomarkers have become a valuable tool in environmental assessment, since they contribute to predicting contaminants in monitoring programmes. This study aimed to investigate the toxicity of heavy metal pollution in Lake Qarun using a multibiomarker approach (morphological, oxidative stress, genotoxicity, stress proteins) in Solea aegyptiaca fish. During the winter and summer seasons, water and fish samples were collected from different locations along Lake Qarun; western and norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 131 publications
2
1
0
Order By: Relevance
“…On the other hand, the normal architecture of muscle bundle seems to be distorted with breakdown of muscle bundles as noticed in increase in inter muscle bundles spaces. Such notes agree with earlier studies which demonstrated that muscles are very sensitive to contaminants [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the normal architecture of muscle bundle seems to be distorted with breakdown of muscle bundles as noticed in increase in inter muscle bundles spaces. Such notes agree with earlier studies which demonstrated that muscles are very sensitive to contaminants [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we assessed the oxidative DNA damage (8-OHdG) from the liver tissue of fish exposed to contaminated environments. The levels of 8-OHdG in aquatic species have been studied as a biomarker of oxidative stress caused by contamination, showing increased levels in populations exposed to higher contamination burdens [49,50]. In our study, increased PAH metabolite concentrations in dabs, but not flounders, were related to higher oxidative DNA damage levels, suggesting that PAH metabolism is linked to increased DNA damage in dabs.…”
Section: Discussionsupporting
confidence: 52%
“…The HSI in the Laucala Bay mullet was relatively lower than in the Ba River Delta. An increase in HSI may indicate an increase in liver size and/or lipid content and is associated with liver function deterioration, as demonstrated in similar studies 27,34,35 . The HSI values re ected in samples from the Ba River Delta generally indicate poor environmental quality.…”
Section: Discussionmentioning
confidence: 54%